2022
DOI: 10.1021/acsnano.2c07347
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronics of Atomic Metal–Semiconductor Interfaces in Tin-Intercalated MoS2

Abstract: Metal−semiconductor interfaces are ubiquitous in modern electronics. These quantum-confined interfaces allow for the formation of atomically thin polarizable metals and feature rich optical and optoelectronic phenomena, including plasmon-induced hot-electron transfer from metal to semiconductors. Here, we report on the metal−semiconductor interface formed during the intercalation of zerovalent atomic layers of tin (Sn) between layers of MoS 2 , a van der Waals layered material. We demonstrate that Sn interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[142] For example, Han et al have demonstrated the formation of intercalated Cu carpets within MoS 2 via a vacancy-mediated atomic diffusion strategy. [143] Up to now, a myriad of approaches have been developed for the atomic intercalation of various non-noble metals spanning Fe, [144] Co, [145] Sn, [146,147] Cu, [148] etc. In this respect, it is theoretically feasible to integrate non-noble metal optical antennas within 2DLMs through atomic intercalation techniques to improve their interaction with the incident light.…”
Section: Non-noble Metal Optical Antenna Promoted 2dlm Photodetectorsmentioning
confidence: 99%
“…[142] For example, Han et al have demonstrated the formation of intercalated Cu carpets within MoS 2 via a vacancy-mediated atomic diffusion strategy. [143] Up to now, a myriad of approaches have been developed for the atomic intercalation of various non-noble metals spanning Fe, [144] Co, [145] Sn, [146,147] Cu, [148] etc. In this respect, it is theoretically feasible to integrate non-noble metal optical antennas within 2DLMs through atomic intercalation techniques to improve their interaction with the incident light.…”
Section: Non-noble Metal Optical Antenna Promoted 2dlm Photodetectorsmentioning
confidence: 99%
“…Dimensionally restricted materials synthesis such as functional nanowire fabrications [113][114][115][116] have important roles in the nanoarchitectonics strategies. Other types of nanofunctional structures, such as those concerning the electrical properties of heterojunctions of metal-semiconductor materials [117,118] and the physical properties at direct bonding interfaces, [119,120] would also contribute to the nanoarchitectonics approaches. Although this article focuses mainly on optics and electricity properties, the mechanical properties and reliability are also important for nanoscale metals and semiconductors.…”
Section: Summary and Short Perspectivesmentioning
confidence: 99%
“…Intercalation has been experimentally proved to be feasible in common 2D materials including graphene, [ 72 ] phosphorene, [ 73 ] and MoS 2 , [ 74,75 ] but still needs further study for commercialization. Borophene is an excellent conductor, Fermi velocity of carriers is even faster than graphene with Dirac Fermions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, appreciable catalytic performance can be obtained by intercalation of sandwich-like X/M/X structure of transition metal dichalcogenide, [10][11][12][13] layered double hydroxides, [66][67][68] and Mxenes. [16,[69][70][71] Intercalation has been experimentally proved to be feasible in common 2D materials including graphene, [72] phosphorene, [73] and MoS 2 , [74,75] but still needs further study for commercialization. Borophene is an excellent conductor, Fermi velocity of carriers is even faster than graphene with Dirac Fermions.…”
Section: Introductionmentioning
confidence: 99%